Etika Kecerdasan Buatan Berbasis Maqasid as-Syariah - M. Minanur Rohman (Muntaha Noor Institute, 2025)
ABSTRACT: The technological advancements of the twenty-first century, driven by the exponential rise of artificial intelligence (AI), have ushered in a new era offering numerous conveniences. However, the development of AI has also raised ethical questions. This article aims to investigate the ethical concerns by exploring the consequences of AI and interrogating its various ethical dimensions. The paper explains the ethical implications of AI advancements and proposes an AI ethics framework based on Maqasid as-Syariah (the objectives of Islamic law) as an alternative ethical system for governing AI. The article concludes that this distinct Islamic virtue-based ethics approach can be utilized to holistically explore ethical issues related to AI due to its ontological foundation and rich tradition. Maqasid-based ethics is grounded in five fundamental components: the preservation of life, religion, intellect, lineage, and wealth. This Maqasid-based AI ethics can serve as a valuable addition to the global discourse on AI ethics